Élévation du niveau marin dans les îles intertropicales des océans Pacifique et Indien - Gérard Beltrando (Territoire en Mouvement)
The sea level of global ocean shows a positive trend since the middle of the XIXth century with acceleration since the 1990s. This trend increases the risk of flooding which is mainly due to episodes of disturbed weather (tropical cyclone, polar front...) and already weakens coastlines, sandy atolls and wetlands. Many lower latitudes islands are affected by this phenomenon, but their vulnerability is mainly due to the combination of human actions and concentration of activities on the coast. In front of this phenomenon, local authorities concerned have not the same possibility of response with viable solution. In the extreme case, some small islands with lacking arable land, displacement of populations may be the only option, but that should only affect a small fraction of the population. The problems caused by all the environmental changes, mainly attributable to human actions should have more important consequences than just the effects of a mean sea level rise.